Equity Home-Bias : A Suboptimal Choice for UK Investors? - Antoniou, Antonios; Olusi, Olasupo; Paudyal, Krishna (2012)
In spite of the popularity of international portfolio diversification theory, extant empirical literature shows that investors prefer domestic assets and as a result, many studies argue that investors' portfolios are largely suboptimal. This paper examines whether British investors need to diversify their portfolios internationally to gain performance benefits from international markets or can they obtain these benefits by mimicking the portfolios with domestically traded assets. The results confirm that it is possible to mimic the performance of foreign equity with domestic equity. Indeed, the pay-offs from homemade portfolios outperform those from international portfolios regardless of the periodic variation in the overall performance of the UK market vis-a-vis foreign markets. The superiority of homemade portfolio is more prominent in recent years and is enhanced by the increased internationalisation of developed capital markets. Therefore, investors' home bias is not suboptimal.